Lifestyle changes in mitigation pathways: policy and scientific insights. (29th December 2020) - Saujot, Mathieu; Le Gallic, Thomas; Waisman, Henri
Abstract: Lifestyle changes are key factors of the climate mitigation challenge because they drive the demand for energy, goods and food. They have received growing attention in the development and assessment of mitigation pathways, one of the key approaches used to inform mitigation policies. This paper contributes to this emerging literature by examining the political and scientific implications of integrating lifestyle changes into mitigation pathways. We analyse a large sample of pathways, supplemented by interviews with practitioners, to provide a perspective relevant to both scenario production practices themselves and the science-policy process in which they are included. We use three illustrative pathways to describe what it means to explore lifestyle changes and how this exploration can be conducted (indicators, dimensions, precision). We summarize the observed benefits of the explorations of lifestyle changes in scenario production by considering three main contributions of scenarios to policy decision-making: explicit knowledge, mediation tools and framing power. We also discuss why the integration of lifestyle changes poses a potential challenge to the robustness and reliability of pathway production methodologies, which is a condition for their policy-relevance. We therefore argue that the implications of this integration need to be carefully characterized in order to maximize the policy relevance of the analysis without compromising the robustness of the scenario development and assessment process. The nature of lifestyles, which reflect values and preferences and require a multidisciplinary approach, raises significant policy neutrality challenges and scientific challenges. Overcoming these challenges can lead to more policy-relevant pathways: we describe existing approaches in the literature and analyse their contributions and limitations.